PENANGANAN PERNIKAHAN WISATAWAN ASING OLEH GEREJA KRISTEN PROTESTAN BALI (GKPB) - Ni Made Rai Erawati (Politeknik Negeri Bali, 2014)
Tourism is a thriving industry in Bali that has lasted many years. This study has traced a small part of development of tourism in Bali. Interest of the tourists visiting Bali has improved because of culture, nature, and other tourist attractions. One of the cultural activities done by tourist in Bali is wedding. Wedding ceremonies mostly handled by wedding agents, travel agent, hotel or other organization, such as religion organization done by Protestant Christian Church in Bali, who has an institution which is called Bali Church Wedding. The purpose of this study is to see how Bali Church Wedding organise wedding in correlation with wedding agents, travel agents, hotels and other organizations. Beside that to see the other impact of the weddings in Bali, venue used by the couple and the posedure of the wedding in Bali. The study found several findings that may help GKPB to improve the interpersonal skill of their staffs in handling the wedding ritual and participate in the wedding party. Beside that there is a need to formwedding agent association in Bali so there will be a same system in offering the budget for the servise of the religious institution.